AN ANALYSIS OF THE ANXIETY IN SPEAKING PERFORMANCE OF THE THIRD SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Syakila, Devi; Azhar, Fadly; Jismulatif, Jismulatif (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is aims to find out the levels of students’ speaking and the dominant type of anxiety that occured in speaking performance of the Third Semester Students of English Study Program Fkip Universitas Riau. The research design of the research was quantitative descriptive research and the population of the research was third semester students of English study program fkip Universitas Riau. Thus, 30 participants selected from the third semester students of English Study Program Universitas Riau by using a proportional sampling technique. The data were collected through questionnaire. The questionnaire was adapted from FLCAS (Foreign Language Classroom Anxiety Scale) designed by Horwitz et al (1986). The result of the questionnaire shows that the students’ speaking anxiety is overall in the anxious level. There were six students (20%) in the level of very anxious, thirteen students (43.3%) in the level of anxious, nine students (30%) in the mildly level, one student (3%) in the relaxed level, and also one student (3%) in the level very relaxed. The result from grouping based on FLCAS type found that “test anxiety” was the main factor that causes students to feel anxious about 18 (60%) students, followed by the “communication apprehension” factor became the second factor with 16 (53%) students, then the last factor was “fear of negative evaluation” with 16 (53%) students. It concludes that the highest anxiety scale that occurs in “anxious” caused by test anxiety.Key Words: Analysis, Speaking, Anxiety In Speaking Performance.